Observations of Martian layered ejecta craters and constraints on their formation mechanisms. (18th March 2015) - Li, Li; Yue, Zongyu; Di, Kaichang; Peng, Man
Abstract: The formation mechanism of layered ejecta craters on Mars has remained a topic of intense debate since their discovery. In this study, we perform a global morphological analysis of Martian layered ejecta craters using Thermal Emission Imaging System (THEMIS) images and Mars Orbiter Laser Altimeter (MOLA) data. The study focuses on the ejecta morphologies and well‐defined distal rampart characteristics associated with 9945 layered ejecta craters with a diameter greater than 1.5 km distributed across the entire Martian surface. Data analysis based on the new database provides new information on the distribution and morphological details of the three major layered ejecta morphologies (single layer ejecta [SLE], double layer ejecta [DLE], and multiple layer ejecta [MLE]). Global analysis is applied to the latitudinal distribution of characteristic parameters, including the ejecta mobility, lobateness values, and onset diameter. Our survey of the distribution and characteristics of layered ejecta craters reveals that strong correlations exist between ejecta mobility and latitude, and there is a latitudinal dependence of onset diameter. Our study of Martian layered ejecta craters provides more detailed information and insights of a connection between the layered ejecta morphologies and the subsurface volatiles.